HS-CRP is A Potential Proinflammatory Biomarker in Postmenopausal Women (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Menopause is a normal physiological process of permanent cessation of menstruation resulting from the eventual atresia of almost all oocytes in the ovaries. Risk of inflammation may be increased in menopause due to estrogen deprivation. Inflammatory markers are thought to be associated with development of atherosclerosis & coronary heart diseasein postmenopausal women. Several inflammatory markers like High Sensitivity C-reactive Protein (Hs -CRP) is held responsible for cardiovascular events in the post-menopausal women. In menopause production of Hs -CRP are increased from different cell types. The study was undertaken to estimate the serum high sen- S sitive C-reactive protein (Hs -CRP) level for prediction of Atherosclerotic Cardiovascular Disease (ASCVD) risk due to inflammation in postmenopausal women.Materials and methods: A hospital based observational study was carried out in outpatient Department of Gynecology & Obstetrics (CMCH) & Department of Biochemistry of Chittagong Medical College (CMC) from January 2019 to December 2019. One hundred (100) postmenopausal women aging 50-65 years was included in the study by non-probability consecutive sampling technique. Postmenopausal women were enrolled as cases by their given H/O of cessation of regular menstrual cycle for last one year. Serum Hs -CRP and fasting serum lipid profile were estimated in enrolled cases. Post-menopausal women considered as cases are grouped by the values of serum Hs -CRP according AHA (American Heart Association). Blood  pressure and waist circumference were also recorded.Results: In this studyLow risk, Average risk, and High risk group of Hs -CRP (according AHA) were identified with their frequencies of 9, 44, and 47 respectively. Other parameters of ASCVD risk factors such as lipid profile, Waist circumference, Hypertension were also significantly S S associated with different risk group of serum Hs -CRP in cases. Mean Hs -CRP were (2.13 ± 0.08 mg/L) and (5.5 ± 0.44 mg/L) in average and high risk group respectively in postmenopausal women.Conclusion: This study established increased serum Hs -CRP as a sensitive proinflammatory biomarker for prediction of Atherosclerotic Cardiovascular Disease (ASCVD) risk in postmenopausal women.JCMCTA 2020 ; 31 (2) : 75-81